Thermal calculation of ground contact structures: Correction factors of environment- and structure-dependent effects on the heat transfer coefficient - NAGY , Balázs (International Journal of Computational and Experimental Science and Engineering, 2015)
The heat loss at ground contact structures is taken into consideration in building heat loss calculations. However, the heat loss through the ground depends not only the soil and the building structure, but the environment as well. New calculation methods based on parametrized transient finite element thermal modelling are introduced in the preceding research article [3]. This paper is the further demonstration of the methods’ environment- or structure-depending correction factors which describe the effect of changing climatic conditions, soil composition or the change of the floor’s structure. These corrections are investigated by using finite element computer modeling tools. A comparative analysis of the initial results and the results corrected according to the different environmental- or structural conditions are represented, showing the impacts of the variable circumstances. The study also deals with the three-dimensional thermal effects from the geometric of the building, providing shape correction multiplying factors to the basic building forms of ground contact structures.